Pengaruh Size, ROA dan Leverage Terhadap Struktur Modal Perusahaan di BEI - Ratnawita, Ratnawita; Syahribulan; Bachtiar, Irmah Halimah; Syamsinar; Durya, Ngurah Pandji Mertua Agung (Jurnal EMT KITA, 2024)
This study aims to examine and analyze the effects of firm size, ROA, and leverage on the capital structure of companies listed on the Indonesia Stock Exchange (IDX). The population of this research includes all food and beverage companies listed on the IDX for the 2019-2023 reporting period. The results were obtained both simultaneously and partially. The sampling method used was purposive sampling, resulting in 18 companies as research samples. The analysis technique used in this study is multiple linear regression analysis using SPSS, where the data were tested with the coefficient of determination test (R²), F-test, and t-test at a 5% significance level (0.05). In addition, the data were analyzed using descriptive statistics, and classical assumption tests were also conducted, including tests for normality, multicollinearity, heteroscedasticity, and autocorrelation. The SPSS output showed that the One-Sample Kolmogorov-Smirnov test statistic was 0.132, with residual data having a significance value of Asymp. Tolerance for the three independent variables greater than 0.10, and VIF values below 10, indicating no multicollinearity. The significance values for the independent variables were X₁ (size) = 0.338, X₂ (ROA) = 0.201, and X₃ (leverage) = 0.183. The Durbin-Watson (DW) statistic was 1.873, compared to the Durbin-Watson significance table with N = 90 and three independent variables (K = 3). The regression coefficient (β₁) was 0.003. The regression coefficient (β₂) was 0.042. The R² (R Square) value was 0.937. Variable X₁ (size) had a t-value of 0.084 < t table 0.67735 and a significance value (Sig.) of 0.933 > 0.05. Variable X₂ (ROA) had a t-value of 0.442 < t table 0.67735 and a significance value (Sig.) of 0.659 > 0.05. Variable X₃ (leverage) had a t-value of 10.490 < t table 0.67735.